Model of Digital Education Strategy and School-Based Curriculum in Anticipating LGBTQ+ at Gideon Senior High School - Operahmat Halawa (MASI Mandiri Edukasi, 2026)
The rapid advancement of digital technology, alongside the growing visibility of LGBTQ+ issues in contemporary society, presents significant challenges for Christian-based schools in nurturing students’ character and spiritual development. This study aims to analyze and describe the digital education strategy model and the school-based Christian Religious Education (CRE) curriculum implemented at Gideon Senior High School, Jakarta, in anticipation of students’ potential involvement in the LGBTQ+ community. Employing a qualitative descriptive method with an inductive approach, this research adopts case study and phenomenological perspectives to gain an in-depth and contextual understanding. Data were collected through participatory observation, in-depth interviews with the principal and CRE teachers, and document analysis. The research was conducted from January to April 2025, supported by preliminary observations of LGBTQ+ issues over the previous three years. The findings indicate that integrating digital education strategies into CRE learning significantly enhances the relevance and effectiveness of moral and spiritual instruction. The use of artificial intelligence (AI), digital animations, podcasts, Zoom, and YouTube fosters interactive, engaging learning experiences while supporting teachers in delivering character-based guidance. Moreover, the school-based CRE curriculum emphasises character formation through structured teaching, mentoring, counselling, discipleship, and spiritual practices such as worship, prayer, and fasting. It promotes moral integrity, emotional maturity, self-awareness, responsible decision-making, and a Christ-centred life guided by the Holy Spirit. The study concludes that the synergy among digital innovation, faith-based curriculum, and strong teacher-parent collaboration forms an effective preventive model for holistic Christian education in the contemporary digital era.